2014
DOI: 10.1292/jvms.14-0276
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Mycobacteriosis in an Aborted Thoroughbred Fetus in Japan

Abstract: A male Thoroughbred fetus was aborted on day 251 of pregnancy. Gross and histological examinations detected systemic granulomatous lesions in many superficial and visceral lymph nodes and organs including the liver, tonsils, lungs, thymus, spleen, right thyroid gland and gastrointestinal tract, and suppurative placentitis, pyogranulomatous amnionitis and intralesional acid-fast bacilli were also detected. An examination of the DNA base sequence of the β subunit of RNA polymerase demonstrated that Mycobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…To the best of our knowledge, these MAH strains are the first II‐a/SC3 strains isolated in Japan. One case of equine abortion from MAH infection in Hokkaido was described in 2014 (Sano et al., 2014), but we could not find any epidemiological relationship between that case and ours. Detailed comparisons based on genetic information unfortunately could not be carried out owing to a lack of information on the previous strain.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…To the best of our knowledge, these MAH strains are the first II‐a/SC3 strains isolated in Japan. One case of equine abortion from MAH infection in Hokkaido was described in 2014 (Sano et al., 2014), but we could not find any epidemiological relationship between that case and ours. Detailed comparisons based on genetic information unfortunately could not be carried out owing to a lack of information on the previous strain.…”
Section: Resultscontrasting
confidence: 69%
“…In horses, most MAH infections have taken the form of tubercular lesions in the liver, spleen, lung tissue, colon, lymph nodes and other organs (Pavlik et al., 2004). Five cases of equine abortion associated with fetal mycobacterial infections have been reported: one case of M. terrae in Australia in 1981 (Tasler & Hartley, 1981), one case of MAC infection in the USA in 1991 (Cline et al., 1991), one of MAC in Canada in 1996 (Helie & Higgins, 1996), one case of a novel Mycobacterium species in 2012 (Johnson et al., 2012) and one case of MAH in Japan in 2014 (Sano et al., 2014). In this paper, we report an outbreak of MAH infection resulting in 10 equine abortions in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the increased susceptibility to infections has been observed in periparturient cows mainly due to deficient systemic and local immune responses around parturition ( 18 ). It was suggested that bacterial invasion of the chorionic surface and subsequent hematogenous spread might be responsible for causing the fetus' systemic infection in equine species ( 11 ). Since camel placenta is epitheliochorial and resembles equine placenta, and hence this infectious route can also be possible in camels.…”
Section: Discussionmentioning
confidence: 99%
“…due to infection with M. bovis (Sarradell et al, 2015;Hlokwe et al, 2016), infections by M. avium are considered the most common cause of equine mycobacteriosis (Pavlik et al, 2008;Sano et al, 2014). Within the MAC complex, infections with M. avium subsp.…”
mentioning
confidence: 99%
“…Enteric infection is associated typically with granulomatous enteritis and colitis (Sarradell et al, 2015;Mönki et al, 2016). Less frequent manifestations include pneumonia (Ryhner et al, 2009), abortion (Cline et al, 1991;Hélie and Higgins, 1996) and systemic infections (Cline et al, 1991;Sano et al, 2014). Enteric infections are thought to be facilitated by ulceration related to parasitism (Pavlik et al, 2004).…”
mentioning
confidence: 99%